2016
DOI: 10.1111/jgs.14302
|View full text |Cite
|
Sign up to set email alerts
|

Pain Treatment of Underserved Older African Americans

Abstract: Older adult African Americans who experience pain are especially at high-risk for under assessment and treatment. This study examined the patterns and correlates of pain medication use that include the following: severity of pain, medical conditions, and access to care. Four hundred African American older adults aged 65 years and older were recruited from 16 churches located in South Los Angeles. Structured face-to-face interviews and visual inspection of each participant’s medications were conducted. More tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 24 publications
4
22
0
1
Order By: Relevance
“…This aligns with much of the existing research which has shown that low SES is related to higher risk for incidence of pain, greater severity of pain, as well as, greater disability and distress from pain (18)(19)(20)(21)(22). While the previous research demonstrated the relationship between financial difficulties and several aspects of pain, the current study shows this relationship holds for AA samples specifically, who are especially at risk for pain mismanagement or undertreatment (71)(72)(73)(74).…”
Section: Adjusted Correlates Of Financial Difficultiessupporting
confidence: 86%
“…This aligns with much of the existing research which has shown that low SES is related to higher risk for incidence of pain, greater severity of pain, as well as, greater disability and distress from pain (18)(19)(20)(21)(22). While the previous research demonstrated the relationship between financial difficulties and several aspects of pain, the current study shows this relationship holds for AA samples specifically, who are especially at risk for pain mismanagement or undertreatment (71)(72)(73)(74).…”
Section: Adjusted Correlates Of Financial Difficultiessupporting
confidence: 86%
“…In those studies, the most frequent PIMs were represented by PPIs, drugs without an indication, NSAIDs, and benzodiazepines, whereas PPOs were represented by statins, antiplatelet agents, calcium, and vitamin D. [24][25][26][27] The most prevalent PIMs observed in our study are in accordance with those from other studies. [28][29][30][31][32] A study in Romania by Primejdie et al in 2016 using the STOPP/ START criteria of 2008 showed that the drug class with the highest percentage of use was NSAIDs (56.66% of outpatients and 35.63% of hospitalized patients), followed by benzodiazepines. That study did not assess PPOs.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is not surprising that there was a high prevalence of NSAID consumption by participants, especially in those with HTN. Given that OTC NSAIDs are more accessible (Booker, Herr, et al, 2019), NSAIDs are commonly used by African Americans in later life (Yazdanshenas et al., 2016). The second potential biological–behavioural syndemic is that of chronic pain‐HTN and NSAID use in African American, which could be fuelled by lack of access to prescription medication, inadequate knowledge drug–disease interaction and fear of addiction of opioids (Booker, Herr, et al, 2019; Park, Manotas, & Hooyman, 2013).…”
Section: Discussionmentioning
confidence: 99%